A conservação preventiva da coleção de paleoinvertebrados do Museu Paraense Emílio Goeldi: análise de microambiente - TRINDADE, Doriene Monteiro (2019)
A museum storage is the space where collections are kept most of the time and therefore it is important that it conforms to the principles of preventive conservation - indirect actions of preservation that aim to minimize degradation agents of museum collections in different environments - macro (e.g. the storage, the exhibition area) or micro (e.g. cabinets, display cases, packaging). This works aimed to analyze the microenvironments found in the Emilio Goeldi Museum’s Paleoinvertebrates collection that, being isolated from the external environment, have different climatic characteristics. With the aid of a datalogger programmed to collect data every 30 minutes, humidity and temperature data were collected for two months in the drawers, and two weeks in one of the plastic bags used for storage of fossils. Five bags and two types of foam underwent chemical tests for the presence of unsuitable compounds in their composition: test with glass jars for chemical stability, and the copper wire test, to detect PVC, inappropriate material for use in collections. The average temperature in the cabinets was 23.2°C, with an average variation of 4.8°C. Inside the plastic bag, the average temperature was 23.6°C with a variation of 3.9°C; the relative humidity inside the cabinets was 51.6%, ranging 4.3%. Inside the plastic bag, the relative humidity was 49.1%, ranging 2%. Comparing the values in both microenvironments, it was concluded that these enabled the creation of a more stable microclimate, which favors the conservation, since climate change is currently considered one of the biggest agents of degradation in collections. With respect to chemical testing, out of the 7 support structures tested, only one presented PVC in its composition, however, regarding their chemical stability, all were considered unstable, and unsuitable for use in the collection. Therefore, under current conditions, the Paleoinvertebrates collection’s microclimate presents climate stability, which favors the preservation of the fossils, because it avoids the acceleration of possible chemical reactions that occur as a result of inadequate packaging. However, it is necessary to replace these unstable materials for more stable ones, such as polyethylene, decreasing even more the risk of damage to this part of Amazon’s fossil heritage.